Influence of Road Traffic Vibration on Micro-Dynamic Response of Precision Instrument Vibration Isolation Platforms - Ying Zhang; Xihui Wang; Chenhu Lu; Kehui Liu; Bo Song (Engineering Proceedings, 2023)
This paper analyzes the impact of environmental vibration caused by road traffic operations on precision instrument vibration isolation platforms. The research results show that there are directional differences in the speed response of the vibration isolation platform caused by vehicle load. The speed response is highest in the horizontal direction perpendicular to the vehicle’s motion. The dominant frequency of the dynamic response of the isolation platform caused by road vehicle loads was concentrated at 2.5 Hz, mainly low-frequency vibrations. The monitoring results are basically consistent with the trend of structural vibration changes in the numerical simulations.